Pathophysiological aldosterone levels modify the secretory activity of cardiac progenitor cells. (5th January 2017) - Wenzel, Kristin; Samal, Rasmita; Hammer, Elke; Dhople, Vishnu M.; Gross, Stefan; Völker, Uwe; Felix, Stephan B.; Könemann, Stephanie
Abstract: Cardiac progenitor cells (CPCs) trigger regenerative processes via paracrine mechanisms in response to changes in their environment. In the present study we explored alterations in the secretory activity of CPCs induced by raised aldosterone levels symptomatic for heart failure. The cytokine profile of the supernatant of CPCs that were treated with the mineralocorticoid showed an induction of interleukin-6 secretion. Mass spectrometric analyses revealed an increase in the abundance of secreted proteins associated with regeneration and cell migration like gelsolin and galectin-1. Differential regulation of proteins associated with the extracellular matrix further points to an activation of cell migration. In response to supernatant, migration and proliferation were induced in CPCs, indicating a potential role of paracrine factors in the activation of CPCs from other regions of the heart or extra-cardiac sources. Changes in the secretory activity of CPCs might aim to compensate for the detrimental actions of aldosterone in heart failure. Graphical abstract: Highlights: Aldosterone influences the secretome of cardiac progenitor cells. Supernatant of aldosterone treated cells induces migration and proliferation. Mineralocorticoid treatment increases interleukin-6 secretion of Sca-1 cells. Secretion of regenerative marker is augmented under aldosterone treatment.